PENGARUH PROFITABILITAS, STRUKTUR MODAL, KEBIJAKAN DEVIDEN, DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN (Studi Kasus Perusahaan Manufaktur Yang Go Publik di Bursa Efek Indonesia) PERIODE 2010 - 2014 - Sri Ayem; Ragil Nugroho (Jurnal Akuntansi, 2016)
This research aims to find empirical evidence about the influence of profitability on firm value. To find empirical evidence about the influence of capital structure on firm value. To find empirical evidence about the influence of dividend policy on firm value. To know more about the influence of empirical evidence Investment Decision on firm value. To know more about the influence of empirical evidence profitability, capital structure, dividend policy and investment decisions simultaneously on firm value. Variables of this research are Profitability, Capital Structure, Dividend Policy, Investment Decisions and firm value. The type of data research is secondary data, it is manufacturing company's financial statements the period of 2010 - 2014. The analysis technique used is multiple linear regression with a significance level of 5%. The research results show that profitability have a positive and significant effect on firm value. Capital structure does not affect the firm value. Dividend policy is positive and significant effect on firm value. Investment policy and significant positive effect on firm value. Simultaneously profitability, capital structure, dividend policy and investment decisions are have significant effect on firm value. The effect of profitability, capital structure, dividend policy, and investment decisions to firm value by 37.5% while the rest influenced by other factors not included in the research model. Keywords: Profitability, Capital Structure, Dividend Policy, Investment Decisions and Firm Value